Efficacy of 5% methylene blue photodynamic therapy in the treatment of potentially malignant oral disorders: a randomized, double-blind, controlled trial - Santos de Freitas Silva, Brunno; Mendes Rocha, Reuber; Paiva Prudente, Tiago; Moraes de Oliveira Lenza, Milena; Lobato Ferreira Ferraz, Daniel; Mezaiko, Eleazar; do Couto Lima Moreira, Francine; Yamamoto-Silva, Fernanda Paula (International Journal of Clinical Trials, 2024)
Background: Potentially malignant oral disorders (PMOD) play a vital role in the secondary prevention of oral cancer, especially considering the difficulty in identifying specific risk factors. Oral leukoplakia (OL), the most common PMOD, has a variable malignant transformation rate. Photodynamic therapy (PDT) emerges as a promising alternative in treating these conditions. This approach is particularly valuable for extensive lesions or patients with contraindications to conventional treatments. Despite promising results, the choice of photosensitizer agent still lacks consensus. The aim of this study is to evaluate the efficacy of PDT with 5% methylene blue compared to 20% aminolevulinic acid (ALA) in the treatment of OL. Methods: This is a randomized, controlled, double-blind clinical trial with a non-inferiority testing approach. Patients will be allocated into two groups: leukoplakia experimental group (PDT with methylene blue) and leukoplakia control group (PDT with ALA). The analysis of results will be based on primary outcomes (clinical remission) and secondary outcomes (histological/cytological worsening, lesion appearance, symptoms, function, psychological impact, economic impact, treatment adherence, and adverse effects). Allocation will be performed in a randomized and stratified manner, ensuring equivalence between groups. Cost-effectiveness analysis will consider the direct costs of treatment from both professional and patient perspectives. Conclusions: This study aims to contribute to the establishment of an effective, safe, and accessible treatment protocol for the most prevalent PMOD, filling an important gap in the scientific literature and providing guidelines for future clinical practices.